2020
DOI: 10.6026/97320630016004
|View full text |Cite
|
Sign up to set email alerts
|

Metascience in Bioinformation

Abstract: Metascience refers to the systematic process that uncovers, builds, evaluates, organizes and disseminates scientific advances. It is the principal tool at the disposal of the society to combat the debilitating effects of "false information" on health related data and its constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…EBHC is a product of metascience, the hypothesis-driven process of systematic inquiry of the best available evidence, and its optimal application in practice [33,34]…”
Section: Evidence-based Healthcare (Ebhc)mentioning
confidence: 99%
See 2 more Smart Citations
“…EBHC is a product of metascience, the hypothesis-driven process of systematic inquiry of the best available evidence, and its optimal application in practice [33,34]…”
Section: Evidence-based Healthcare (Ebhc)mentioning
confidence: 99%
“…The best available evidence is derived systematically from the stringent, hypothesis-driven process of research synthesis, and is reported as systematic reviews [33][34][35][36][37][38][39][40][41][42]. Across any field of inquiry, research evidence usually results from excellent science, but it may also emerge from scientific reports that suffer from serious methodologically flaws and biases.…”
Section: Evidence-based Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Rigorous evidence-based analysis should seek to eliminate both misinformation (inaccurate information created by honest mistake) and disinformation (inaccurate information used for intentional deceit). 118 The profession should adopt a stringent peer-review process to eradicate poor science, and to abolish the publication of low-quality articles and predatory journals, in order to rebuild lost confidence within the public and the profession. 119…”
Section: Clinical Recommendations and Future Directionsmentioning
confidence: 99%
“…Clinical guidelines should be developed from sound principles of evidence‐based dentistry, and clinicians should be better trained to develop critical analytical skills, 117 which call for improved curriculum design in dental schools and continuing professional development events. Rigorous evidence‐based analysis should seek to eliminate both misinformation (inaccurate information created by honest mistake) and disinformation (inaccurate information used for intentional deceit) 118 . The profession should adopt a stringent peer‐review process to eradicate poor science, and to abolish the publication of low‐quality articles and predatory journals, in order to rebuild lost confidence within the public and the profession 119…”
Section: Clinical Recommendations and Future Directionsmentioning
confidence: 99%